2020
DOI: 10.3389/fpls.2020.00128
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the MdKNOX Gene Family and Characterization of Its Transcriptional Regulation in Malus domestica

Abstract: Knotted1-like Homeobox (KNOX) proteins play important roles in regulating plant growth, development, and other biological processes. However, little information is available on the KNOX gene family in apple (Malus domestica Borkh.). In this study, 22 KNOX genes were identified in the apple genome. The gene structure, protein characteristics, and promoter region were characterized. The MdKNOX family members were divided into three classes based on their phylogenetic relationships. Quantitative real-time PCR ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 68 publications
2
22
0
Order By: Relevance
“…Subsequently, more KNOX genes were identified and characterized in other plant species [13]. The KNOX genes seem to have a limited number in different species, for example, 8 in Arabidopsis, 13 in rice, 12 in maize, 15 in poplar [12], 10 in peach [10], 22 in apple [27], and 18 in pear [24]. Furthermore, the number of KNOX genes among different plant species seems not to correlate with their genome sizes, which was further confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, more KNOX genes were identified and characterized in other plant species [13]. The KNOX genes seem to have a limited number in different species, for example, 8 in Arabidopsis, 13 in rice, 12 in maize, 15 in poplar [12], 10 in peach [10], 22 in apple [27], and 18 in pear [24]. Furthermore, the number of KNOX genes among different plant species seems not to correlate with their genome sizes, which was further confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both in the natural context of KNOX function in the SAM and upon ectopic KNOX expression in Arabidopsis leaves, reducing activity of the GA growth regulators could promotes meristematic activity [38]. Recently, studies in apple indicated that expressions of KNOX genes are also inducible by exogenous phytohormones [17,27]. For example, MdKNOX19, a Class II KNOX gene regulating apple fruit and seed developments through ABA signaling, was significantly up-regulated when applied ABA to apple leaves, fruits, and seeds [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The class II subfamily lacks phenotypic due to mutations; however, there have been relatively few previous studies. In brief, KNOX genes are involved in the growth and development of different tissues and organs in different species [ 26 , 27 , 28 ]. Plants must constantly adjust their physiological processes to adapt to changes in the external environment [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first KNOX gene to be identified in plants was Knotted1 (Kn1) in maize (Vollbrecht et al, 1991). Following this discovery, the KNOX gene was identified in more and more plants (Gao et al, 2015), such as Arabidopsis, rice, poplar, cotton, apple and so on, and the functions of some KNOX genes have been deeply studied (Mukherjee et al, 2009;Xiong et al, 2018;Ma et al, 2019;Jia et al, 2020). However, little information is available on the KNOX gene family in the important food crop wheat (Triticum aestivum L.).…”
mentioning
confidence: 99%